Robust flame-retardant, super mechanical laminate epoxy composites with tunable electromagnetic interference shielding. (September 2022) - Wang, B.; Yin, Z.; Zhang, Y.; Jia, P.; He, R.; Yu, F.; Hu, Y.
Abstract: Considering the high strength, excellent heat resistance, and fast-curing properties of room temperature epoxy (EP), it has been extensively used in positioning, assembly, repair, sealing, potting, and other applications. However, lack of reasonable structural design and precise composition control, it is hard to accomplish 5G communication and resist harsh environments, which are urgently needed for practical applications. Therefore, a smart electromagnetic interference (EMI) device with strong designability has been prepared through a dipping/supplying and hand-laying/vacuum bag pressing, which could not only show excellent shielding effectiveness (SE) but also achieve tunable SE derived from the content of Ti3 C2 Tx . Meanwhile, thanks to the triangle understanding of composition, structure, and properties, we find a promising flame retardant (ammonium polyphosphate: APP). Our results display that with a V0 rating in the UL-94 test and the LOI value as high as 40% for AEP-RFT1.2, the peak heat release rate (pHRR) and total heat release (THR) of AEP-RFT1.2 are reduced by 77.6% and 51.3%, respectively. Besides, the resultant SE of AEP-RFT1.2 can surpass 30 dB in the X band, which is enough for commercial use. This work provides a facile and efficient strategy to fabricate robust flame retardancy, super mechanical strength, and tunable electromagnetic interference shielding room-temperature cured laminate epoxy composites, which also gives an avenue for industrial applications. Graphical abstract: Image 1 Highlights: A smart EMIdevice has been prepared by manual layering & vacuum bag pumping method. The tensile strength and elongation at break of AEP-RFT1.2 were 51.2 MPa and 9.26%, respectively. AEP-RFT1.2 achieves a V0 rating and the LOI value as high as 40%. Tunable EMI SE of AEP-RF1.2 surpasses 30 dB in the X band.